2005
DOI: 10.1080/09273940590909167
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE Effect of Ketotifen Fumarate, Olopatadine, and Levocabastine on Ocular Active Anaphylaxis in the Guinea Pig and Ocular Immediate Hypersensitivity in the Albino Rat

Abstract: In the guinea pig model, ketotifen was more effective than olopatadine and levocabastine at reducing conjunctival edema and vascular permeability in eyelids and eyeballs. In the rat model, ketotifen was more effective at reducing vascular permeability in eyelids than olopatadine and levocabastine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…However, ketotifen is a compound with strong anti-anaphylactic and antihistaminic properties both in experimental animals and humans [19]. Ketotifen not only blocks H 1 receptors and stabilizes mast cells, it also reduces intracellular calcium levels in activated mast cells [20,21]. In the present study, we did not note an effect of Buk music on mast cell stabilization and intracellular calcium level.…”
Section: Discussioncontrasting
confidence: 51%
“…However, ketotifen is a compound with strong anti-anaphylactic and antihistaminic properties both in experimental animals and humans [19]. Ketotifen not only blocks H 1 receptors and stabilizes mast cells, it also reduces intracellular calcium levels in activated mast cells [20,21]. In the present study, we did not note an effect of Buk music on mast cell stabilization and intracellular calcium level.…”
Section: Discussioncontrasting
confidence: 51%
“…28 To determine the effect of anti-allergic agents on the conjunctival vasculature, 16 mg/kg of EB (30 mg/mL in sterile saline) was then injected into the cervical vein immediately prior to challenge. 29…”
Section: Methodsmentioning
confidence: 99%
“…Although cyclosporine A is reported to inhibit degranulation of mast cells in vitro, 12,13 the effect of cyclosporine A on the early-phase reaction is not well studied in vivo. We therefore examined the effect of cyclosporine A eye drops in the early-phase reaction such as plasma exudation and mast cell degranulation in the conjunctiva 30 min after RW challenge in actively sensitized to that shown in Figure 1B because administration of cyclosporine A eye drops 3 h before RW challenge signifi cantly decreased the increase in vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that anti-histamine is a potent inhibitor of the early-phase reaction. 12,14 Ketotifen instillation showed the most potent inhibitory effect on plasma exudation after single RW challenge. mice.…”
Section: Effect Of Cyclosporine a Eye Drops On The Itch-scratch Respomentioning
confidence: 91%